The Peshdar Plain Project, 2015-2016. A Major Neo-Assyrian Settlement on the Empire’s Eastern Border - Radner, Karen; Kreppner, Janoscha; Squitieri, Andrea (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
The Peshdar district is part of the province of Sulaymaniyah in the Kurdish Autonomous Region of Iraq. It is situated directly on the border with Iran (Figure 1). The Peshdar Plain Project was inaugurated in 2015 and aims to uncover the ancient history of this understudied area with a focus on the 9th-7th centuries BC when the Neo-Assyrian Empire controlled the region. The project initially focused on two sites: Gird-i Bazar (henceforth Bazar, 36° 8' 18’ N, 45° 8' 28’ E), a shallow mound situated in the plain, and the more impressive Qalat-i Dinka (henceforth Dinka, 36° 8' 12’ N, 45° 7' 57’ E; altitude: 579m), looming high over the Lower Zab. However, the results of geoarchaeological work conducted in 2015 by Mark Altaweel and the survey of the Mission Archeologique Française du Gouvernorat de Soulaimaniah (MAFGS), directed by Jessica Giraud, suggested that Bazar and Dinka are parts of one extended site belonging to the Neo-Assyrian period (Radner et al. 2016: 23-36) and this was confirmed in autumn 2016 by the results of the magnetometer survey conducted by Jörg Fassbinder between Bazar and Dinka. Our preliminary designation for the entire site is ‘Dinka settlement complex’.